Pelayanan PT. Lion Mentari Air Rute Jakarta - Yogyakarta - Lukiana Lukiana (WARTA ARDHIA, 2011)
The growth number of passenger of air transportation increased rapidly as an indicator of industrial development of air transport services must be balanced with the service and information from the airlines' services to service users in order to feel the services delivered as expected. Airline companies should be able to provide services as required passengers who have different characters. Services provided by the airlines in carrying out its activities are divided into 3 (three) groups: service with a maximum standards (full service), service with a medium standards (medium service) and services with minimum standards (no frills). Passengers PT. Lion Mentari Air Jakarta – Yogyakarta route with minimum service standards (no frills) is a sample in this study. The results of calculations using the average performance (X) 3.56 and the average expectation of passengers(Y) 4.45 indicating that the performance of PT. Lion Mentari Air is still low compared with the expectations of passengers. The results of the analysis of customer satisfaction index of 17 indicators of service provided through the 71.14% scored less satisfactorily interpreted so that the performance of PT. Lion Air still needs refinement and improvement.